Pengaruh Kualitas layanan terhadap Kepuasan Pelanggan di Salon Kecantikan Erlin Beauty Gallery - Nadia Azzahra; Merita Yanita (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the influence of service quality on customer satisfaction at Erlin Beauty Gallery beauty salon, West Pasaman. In an era of increasingly tight competition in the service business, service quality is a key factor in maintaining customer loyalty. This study uses a quantitative approach with a survey method. Samples were taken as many as 45 respondents using a simple random sampling technique. The research instrument was arranged based on five dimensions of, namely tangibles, reliability, responsiveness, assurance, and empathy. The results showed that service quality has a positive and significant effect on customer satisfaction at the beauty salon at Erlin Beauty Gallery. Service quality has a significant effect on customer satisfaction at Erlin Beauty Gallery Beauty Salon with a significant value of 0.000 ≤0.05 and a t count value of 5.504≥ t table 2,017, it can be concluded that service quality has a positive and significant effect on customer satisfaction at Erlin Beauty Gallery beauty salons. Therefore, it is important for beauty salons to be able to improve the quality of service provided to customers so that customer satisfaction is met and they decide to undergo treatment at ErlinBeuty.